Academic Achievement and its Psychological Correlates on School Students: The Impact of Social Variables on Academic Performance (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Based on the nature of the research issue, the technique chosen for this study willdetermined. The research will have descriptive concept of co-relational research as a researchtechnique. In order to investigate the connection between interests, tensions, and deviant behaviors aswell as to learn its effect on the academic performance of high school pupils, the researcher chose adescriptive co-relational researcher design. Various quantitative data collection methods may be used.The researcher has chosen 16 schools randomly from each district. Research in the field of educationonly has value if it leads to meaningful changes in the classroom as a result of the It may be claimed thatthe results of this research would help students if they were used to boost their grades. The study'sfindings provide empirical support to the thesis that kids' academic success in school is affected notonly by individual disparities in ability and interest but also by social variables such as community,caste, religious, cultural, and regional conflict.